The starch solution : eat the foods you love, regain your health, and lose the weight for good! - McDougall, John A. (Rodale, 2013)
Fear of carbs has taken over the diet industry for the past few decades--the mere mention of a starch-heavy food is enough to trigger an avalanche of shame and longing. Here, diet doctor and board-certified internist John A. McDougall, MD, and his kitchen-savvy wife, Mary, show that a starch-rich diet can actually help you lose weight and prevent a variety of ills. By fueling your body primarily with carbohydrates rather than proteins and fats, you'll feel satisfied, boost energy, and look and feel better.--From publisher description.